2022
DOI: 10.48550/arxiv.2203.01484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Radiative Hydrodynamic Modeling of the Near-Surface Shear Layer in the Solar Convection Zone

Abstract: Understanding effects driven by rotation in the solar convection zone is essential for many problems related to solar activity, such as the formation of differential rotation, meridional circulation, and others. We present realistic 3D radiative hydrodynamics simulations of solar subsurface dynamics in the presence of rotation in a local domain 80 Mm-wide and 25 Mm deep, located at 30 degrees latitude. The simulation results reveal the development of a shallow 10-Mm deep near-surface shear layer ("leptocline")… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Concurrently, the fast convective motions in this layer are not constrained by the solar rotation, and they produce a negative shear that, in turn, accelerates meridional motions, producing the observed surface latitudinal velocity (Miesch & Hindman 2011). Recent simulations by Kitiashvili et al (2022) showed that turbulent convection in the upper part of the NSSL can generate radial differential rotation and meridional circulation. However, it is still uncertain how the turbulent correlations generated by nonlocal convection can sustain the solar differential rotation below the NSSL.…”
Section: A Reynolds Stressesmentioning
confidence: 99%
“…Concurrently, the fast convective motions in this layer are not constrained by the solar rotation, and they produce a negative shear that, in turn, accelerates meridional motions, producing the observed surface latitudinal velocity (Miesch & Hindman 2011). Recent simulations by Kitiashvili et al (2022) showed that turbulent convection in the upper part of the NSSL can generate radial differential rotation and meridional circulation. However, it is still uncertain how the turbulent correlations generated by nonlocal convection can sustain the solar differential rotation below the NSSL.…”
Section: A Reynolds Stressesmentioning
confidence: 99%